PICSARR: high-precision polarimetry using CMOS image sensors. Issue 2 (27th January 2023) - Bailey, Jeremy; Cotton, Daniel V; De Horta, Ain; Kedziora-Chudczer, Lucyna; Shastri, Om
ABSTRACT: We have built and tested a compact, low-cost, but very high performance astronomical polarimeter based on a continuously rotating half-wave plate and a high-speed imaging detector. The polarimeter is suitable for small telescopes up to ∼1 m in aperture. The optical system provides very high transmission over a wide wavelength range from the atmospheric ultraviolet cut-off to ∼1000 nm. The high quantum efficiency, low noise, and high speed of the detectors enable bright stars to be observed with high precision as well as polarization imaging of extended sources. We have measured the performance of the instrument on 20 and 60 cm aperture telescopes. We show some examples of the type of science possible with this instrument. The polarimeter is particularly suited to studies of the wavelength dependence and time variability of the polarization of stars and planets.